Does technological innovation undertaken alone have a real pivotal role? Product and marketing innovation in manufacturing firms. Issue 2 (17th February 2016) - Bartoloni, Eleonora; Baussola, Maurizio
Abstract : This paper investigates the role of non-technological innovation on firms' innovation propensity and performance. We note that emphasis on technological innovation alone is misleading, as a firm's decision to undertake technological innovation brings about a more complex and general process which may involve new attitudes regarding organization and market orientation. We analyse the relationship between product and marketing innovation in manufacturing, focusing specifically on the food industry. We propose a bivariate probit model in which product and marketing innovation are estimated taking into account their reciprocal interactions. This enables us to provide more efficient and realistic estimates of a firm's probability of introducing either a new or improved product or a new marketing technique. In addition, the proposed model provides the determinants of such probabilities.